Programmable embedded system design: A study on sniffer - Tuncer, Taner; Tatar, Yetkin (My University, 2009)
Intrusion Detection Systems (IDS) are designed for capturing the attacks from internet or local area network consisting of various packets and data. Software or hardware IDSs detect the attack considering the network and user parameters. In order to determine the attacks, it is necassary to know some properties of the packets which convey data between networks. Capturing the packets between Networks and computers is called as sniffing. The MAC address, packet size, packet type and IP addresses of the captured packets are given to lDS an input. Thus , the first step is to capture the packet for designing the IDSs. It is very crucial to perform these procedures in real time and fastly. The implementation of real time lDS with a programmable embedded system is a very attactive topic. In this paper, the procedure of capturing the necassary packet and frame is presented to implement a real time lDS programmable embedded system. ©2009 IEEE.
Programlanabilir gömülü sistem tasarimi: Sniffer üzerine bir çalişma
2009 International Conference on Application of Information and Communication Technologies, AICT 2009 -- 14 October 2009 through 16 October 2009 -- Baku -- 79447
Keywords: Computer crime; Embedded software; Embedded systems; Internet protocols; Intrusion detection; Intrusion detection systems; IP addresss; MAC address; Packet size; Packet types; Programmable embedded systems; Real time; Local area networks